Penerapan Metode RAD pada Sistem Informasi Point Of Sales dengan Integrasi Payment Gateway di Kedai Ngopi Ngopi - Hafez Nizamuddin Salim; Ridho Muktiadi; Dimara Kusuma Hakim; Agung Purwo Wicaksono (Politeknik Piksi Ganesha Indonesia, 2025)
Kedai Ngopi Ngopi faces several operational challenges, including the absence of a digital menu display, manual transaction recording, and limited payment methods. This study aims to develop a web-based information system integrated with sales and digital payment functionalities. The system development was carried out using the Rapid Application Development (RAD) method, which emphasizes speed and active user involvement through iterative processes. The developed system includes product management, transaction recording, order notifications, and integration with a digital payment system. Testing results show that the system significantly improves operational efficiency, expands available payment methods, and enhances the overall customer service experience.